2014
DOI: 10.1183/09031936.00009314
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lung function precedes severe respiratory syncytial virus infection and post-respiratory syncytial virus wheeze in term infants

Abstract: It is unknown why respiratory syncytial virus (RSV) causes mild disease in some children and severe disease, requiring hospitalisation, in others. We aimed to assess whether diminished premorbid lung function in healthy term infants predisposes to hospitalisation during RSV bronchiolitis, and to post-RSV wheeze.In a prospective birth cohort study of unselected term healthy children, neonatal lung function was measured before the age of 2 months (n52133). From birth through the first year of life, respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…The MAKI trial has strongly implicated RSV infection as an important mechanism of recurrent wheeze during the first year of life in such infants [66]. A further study from the same group proposed that lower lung function in school-aged children that were previously hospitalized for RSV LRTI cannot only be attributed to the RSV infection itself, but might be partially pre-existent [67]. …”
Section: Resultsmentioning
confidence: 99%
“…The MAKI trial has strongly implicated RSV infection as an important mechanism of recurrent wheeze during the first year of life in such infants [66]. A further study from the same group proposed that lower lung function in school-aged children that were previously hospitalized for RSV LRTI cannot only be attributed to the RSV infection itself, but might be partially pre-existent [67]. …”
Section: Resultsmentioning
confidence: 99%
“…A prospective birth cohort study from the Netherlands evaluated lung function using a single occlusion technique in 2.133 healthy term infants before two months of age . The researchers found that respiratory system compliance was lower in those 18 infants who were hospitalised for RSV bronchiolitis before 12 months of age, compared to 84 nonhospitalised RSV positive children . In the present study, the lung function of former bronchiolitis patients was evaluated with impulse oscillometry at five to seven years of age and with one exception, the lung function reductions, although present in 20%, were reversible .…”
Section: Discussionmentioning
confidence: 54%
“…How often and at what age irreversible lung function reduction after bronchiolitis develops is not known. A prospective birth cohort study from the Netherlands evaluated lung function using a single occlusion technique in 2.133 healthy term infants before two months of age . The researchers found that respiratory system compliance was lower in those 18 infants who were hospitalised for RSV bronchiolitis before 12 months of age, compared to 84 nonhospitalised RSV positive children .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies that measured early‐life lung function suggest the opposite direction of causality. One prospective cohort study showed that increased bronchial responsiveness in infancy was associated with increased risk of severe bronchiolitis and another showed that children with a lower respiratory system compliance, and higher resistance at the age of 2 months, were at greater risk for hospitalization for an RSV infection and wheeze after the infection . However, the latter study group demonstrated that the association of HRV in the first year of life with wheezing at the age of 4 years remained significant after adjusting for lung function measurements at the age of 2 months .…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%